A prognostic baseline blood biomarker and tumor growth kinetics integrated model in paclitaxel/platinum treated advanced non‐small cell lung cancer patients - Francis Williams Ojara; Andrea Henrich; Nicolas Frances; Yomna M. Nassar; Wilhelm Huisinga; Niklas Hartung; Kimberly Geiger; Stefan Holdenrieder; Markus Joerger; Charlotte Kloft (Wiley, 2023)
Abstract Paclitaxel/platinum chemotherapy, the backbone of standard first‐line treatment of advanced non‐small cell lung cancer (NSCLC), exhibits high interpatient variability in treatment response and high toxicity burden. Baseline blood biomarker concentrations and tumor size (sum of diameters) at week 8 relative to baseline (RS8) are widely investigated prognostic factors. However, joint analysis of data on demographic/clinical characteristics, blood biomarker levels, and chemotherapy exposure‐driven early tumor response for improved prediction of overall survival (OS) is clinically not established. We developed a Weibull time‐to‐event model to predict OS, leveraging data from 365 patients receiving paclitaxel/platinum combination chemotherapy once every three weeks for ≤six cycles. A developed tumor growth inhibition model, combining linear tumor growth and first‐order paclitaxel area under the concentration‐time curve‐induced tumor decay, was used to derive individual RS8. The median model‐derived RS8 in all patients was a 20.0% tumor size reduction (range from −78% to +15%). Whereas baseline carcinoembryonic antigen, cytokeratin fragments, and thyroid stimulating hormone levels were not significantly associated with OS in a subset of 221 patients, and lactate dehydrogenase, interleukin‐6 and neutrophil‐to‐lymphocyte ratio levels were significant only in univariate analyses (p value < 0.05); C‐reactive protein (CRP) in combination with RS8 most significantly affected OS (p value < 0.01). Compared to the median population OS of 11.3 months, OS was 128% longer at the 5th percentile levels of both covariates and 60% shorter at their 95th percentiles levels. The combined paclitaxel exposure‐driven RS8 and baseline blood CRP concentrations enables early individual prognostic predictions for different paclitaxel dosing regimens, forming the basis for treatment decision and optimizing paclitaxel/platinum‐based advanced NSCLC chemotherapy.